Antimicrobial, Antioxidant and Cytotoxic Activities of Gomphrena globosa (L.) - Hamiduzzaman, Md; Azam, ATM Zafrul (Bangladesh Pharmaceutical Journal, 2012)
DOI: http://dx.doi.org/10.3329/bpj.v15i2.12590 Bangladesh Pharmaceutical Journal 15(2): 183-185, 2012